84. Ionization chamber calibration for 90Y at OPBG by the ENEA-INMRI portable TDCR. (December 2018) - Donatiello, S.; Capogni, M.; Tapner, M.; Cannatà, V.; Garganese, M.C.; De Felice, P.
Abstract : Purpose: Short-lived beta-emitting radionuclides, such as 90 Y, start to be commonly used in Nuclear Medicine (NM) for Molecular Radiotherapy (MRT). The instruments, such as Ionization Chambers (ICs), typically used in the NM departments for measuring the activity of radiopharmaceuticals need to be calibrated in order to meet the demands of the European Pharmacopoeia[1] . The OPBG IC was then calibrated for the 90 Y by using the ENEA-INMRI portable TDCR counter[2] . Methods: The 90 YCl 3 solution was kindly provided by Sirtex company. A set of 6 sources (2 in 10 mL UG + 20 mL glass vial, 2 in 10 mL H2 O + plastic vial, 2 in 10 mL H2 O + 20 mL glass vial with 20 mg and 40 mg of radioactive in each one) and 1 source in the OPBG IC vial geometry were prepared directly at OPBG to be measured by TDCR and IC devices. Results: The achieved results show that, in the typical operative conditions of a hospital structure, the uncertainties in determining the IC calibration factor are less equal to 2%. Conclusions: The paper highlights how the TDCR-Cherenkov technique, developed at ENEA-INMRI, allows to calibrate on site an IC in use at a Hospital structure. In particular, this technique turns out to be more practical, because the sources to be characterized in activity, for the IC calibration, can be prepared directly in water. The whole work was performed in the framework of the project "Metrology for clinical implementation of dosimetry in Molecular Radiotherapy" (MRTDosimetry) funded by the European Metrology Program for Innovation and Research (EMPIR)[3] .